High-Performance Subtractive Hybridization of cDNAs by Covalent Bonding Between Specific Complementary Nucleotides - Shao-Yao Ying; Shilung Lin (BioTechniques, 1999)
We have developed an improved subtractive hybridization method that provides a fast, simple and reliable isolation of desired different sequences from two compared DNA libraries, one of which contains all unwanted homologues (subtracter) and another contains certain desired heterologues (tester). The DNA library can be made from either mRNA or genomic DNA. An excess amount of modified subtracter DNA from control cells was generated by chemical carboxylation of the pyrimidines to provide covalent affinity to the purines of a natural tester DNA. Hybridization of the control subtracter and the experimental tester DNA was performed with a heat melting and then cool-reassociation technique. The desired different sequences remained in the form of hydrogen-bonded, homologous sequences of both libraries covalently bonded to each other, resulting in no separation during PCR and cloning. Consequently, the DNA sequences obtained from the covalent homology subtraction represent the nucleotide sequences abundant in the tester but rare in the subtracter library.